Pendidikan Lingkungan di Daerah Wisata Pantai Banding: Kampanye “Bawa Pulang Sampahmu” sebagai Dukungan terhadap SDGs 13 Climate Action - Simbolon, Khairunnisa; Darmastuti, Ari; Inayah, Astiwi; Fitria, Arie (Ragom Jurnal Pengabdian Masyarakat, 2024)
Environmental education is an integral part of addressing sustainability challenges in tourist destinations, particularly in coastal areas that are vulnerable to the impacts of climate change. This Community Service activity implements the "Take Your Trash Home" campaign at the Banding Beach Tourist Area as an environmental education initiative supporting the achievement of Sustainable Development Goal (SDG) 13: Climate Action. This activity focuses on conveying the potential impacts of visitor and local community behavior in waste management within the tourist area, as well as exploring its contribution opportunities to climate change mitigation. Banding Beach, as a coastal tourism destination, faces serious challenges related to plastic waste and its impact on the marine environment. The "Take Your Trash Home" campaign was launched as an effort to raise awareness among the public and visitors about the shared responsibility of tackling waste problems. The activity's methodology includes surveys of visitors, interviews with tourism management, and analysis of community behavior data before and after the campaign implementation. The results of the campaign show a significant increase in the participation of visitors and the community in sustainable waste management practices. Increased awareness of the impact of plastic waste on the marine environment and maritime life became an important factor in behavior change. Furthermore, cooperation between the government, tourism managers, and the local community contributed to the success of this campaign.